Effect of alveolex on the bone defects repair stimulated by rhBMP-2: Histomorphometric study - Pereira, Nathalia Terra; Mardegan Issa, Joao Paulo; Do Nascimento, Cassio; Pitol, Dimitrius Leonardo; Ervolino, Edilson [UNESP]; Da Cunha, Marcelo Rodrigues; Pedrazzi, Vinicius (Wiley-Blackwell, 2012)
OBJECTIVE: The aim of this study was to evaluate histomorphometrically the effect of alveolex (Propolis 10%) on the repair of bone cavities in the calvaria of rats. MATERIALS and METHODS: A 5 mm diameter bone defect was made in the calvaria of male Wistar rats using the drill-type trephine. The defects were filled with rhBMP-21Alveolex, rhBMP-2, Alveolex, or coagulum. Twenty-eight animals with seven subjects on each were sacrificed 30 days after surgery and samples were fixed and embedded in paraffin. Histological sections stained by HE (hematoxylin and eosin) were obtained from the calvaria bone defect and analyzed by a differential point-counting method. RESULTS: Group I and II, rhBMP-21Alveolex and rhBMP-2, respectively, presented higher levels of newly formed bone than other groups (P < 0.001). There were not significant differences between groups I and II (P > 0.05). In addition, there was not significant difference between groups III and IV, Control-Coagulum and Alveolex, respectively (P > 0.05). CONCLUSION: Alveolex has increased the bone repair in calvaria defects of rats when associated to rhBMP-2, however without significant differences for rhBMP-2 isolated group; Alveolex isolated group showed the lowest levels of newly formed bone with no significant differences to coagulum group (control). Microsc. Res. Tech. 75: 36-41, 2012. (C) 2011 Wiley Periodicals, Inc.
Keywords: alveolex; rhBMP-2; bone repair; histomorphomety